Dose‐finding trial of tolvaptan in liver cirrhosis patients with hepatic edema: A randomized, double‐blind, placebo‐controlled trial. Issue 1 (27th March 2013) - Okita, Kiwamu; Kawazoe, Seiji; Hasebe, Chitomi; Kajimura, Kozo; Kaneko, Akira; Okada, Mitsuru; Sakaida, Isao; ,
<x xml:space="preserve">Abstract</x> Aim Liver cirrhosis represents the end stage of any chronic liver disease, and it is associated with hepatic edema such as ascites. Many patients with ascites do not respond to diuretic therapy or require administration of diuretics at high doses that can cause adverse events. This 7‐day, multicenter, double‐blind trial of tolvaptan was designed to determine the optimal dose of tolvaptan for producing the intended pharmacological effect in hepatic edema. Methods Liver cirrhosis patients with inadequate diuretic response despite having received a conventional diuretic therapy were enrolled in the trial. Participants were stratified randomly to four groups receiving tolvaptan at 7.5, 15 or 30 mg/day, or placebo as an add‐on to conventional diuretics once daily for 7 days. Changes in bodyweight and abdominal circumference were analyzed. Serum sodium concentrations were measured. Safety assessment was performed. Results Tolvaptan at 7.5–30 mg/day reduced bodyweight and abdominal circumference compared with placebo. Serum sodium concentrations remained within the normal range in all tolvaptan groups. Serious adverse events were not observed, and most common adverse event was thirst. Tolvaptan at 7.5 mg/day showed the maximum change in bodyweight and abdominal circumference together with preferable tolerability. Conclusion Tolvaptan at 7.5 mg/day was considered the optimal dose in liver cirrhosis patients with hepatic edema who showed inadequate response to conventional diuretics.